TRUTH OR DARE GAME MEDIA DEVELOPMENT TO PROVIDE AN UNDERSTANDING OF FAMILY FUNCTION - Rahma, Muthia Haifa; Afiati, Evi; Muhibah, Siti (Jurnal Bikotetik (Bimbingan dan Konseling: Teori dan Praktik), 2024)
This research aims to develop the truth or dare game media to provide an understanding of family functions. The method used is Research and Development (R&D), using the Analysis, Design, Development, Implementation, Evaluation (ADDIE) development model. Data collection techniques by conducting expert feasibility tests on products that have been developed. The data processing technique uses a Likert scale in the form of quantitative and qualitative data. Feasibility test results with experts in the field, media experts 82.5%, material experts 93.3%, language experts 88.6%. The research subjects were 10 students from the Class of 2021 Department of which means it is very suitable for application and the truth or dare game media can increase students’ understanding of family functions.